(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2016)
The aim of this study is to investigate students’ difficulties about the relation between irrational number set, rational number set and real number set. For this purpose, ‘Irrational Number Concept Test’ which was composed of open-ended questions has been developed. The Data collection instrument was applied to 58 students in grade 8 and 50 students in grade 9. Semi-structured interviews with ten students who were selected from different levels with the maximum diversity sampling were conducted. In each grade, it was found that students had difficulties in understanding the relationship between real number set and other number sets. There have been some thoughts such as ‘all of the irrational numbers are not real numbers’ and ‘a number can be both rational and irrational’. It is found that the rate of students that have these wrong thoughts in 8th grades is more than those in 9th grades.